1998
DOI: 10.1177/03635465980260051801
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Muscle Activity in the Posterior Cruciate Ligament-Deficient Knee During Isokinetic Knee Motion

Abstract: We performed electromyographic analyses in 12 patients with posterior cruciate ligament-deficient knees to compare electrical activity in the quadriceps, hamstring, and gastrocnemius muscles between the uninjured and involved limbs. Each patient performed concentric isokinetic knee motion at 30 and 60 deg/sec in both limbs separately. Torques in knee extension and flexion and surface electromyograms from the quadriceps, medial hamstring, and medial gastrocnemius muscles were simultaneously recorded. The uninju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…The velocity of 60°/s has also been used in previous studies relating to hamstring injuries 4,8,56 and in studies investigating hamstring muscle activity during isokinetic testing. 30,35,37 However, other velocities have also been used. 16 Performing eccentric contractions at different speeds is unlikely to have significant effects on torque and muscle activity.…”
Section: Discussionmentioning
confidence: 99%
“…The velocity of 60°/s has also been used in previous studies relating to hamstring injuries 4,8,56 and in studies investigating hamstring muscle activity during isokinetic testing. 30,35,37 However, other velocities have also been used. 16 Performing eccentric contractions at different speeds is unlikely to have significant effects on torque and muscle activity.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that, although the posterior dislocation of the knee was easily reduced manually, the knee easily dislocated again because of gross instability; however, the reduced position could be maintained by repairing the MCL and gastrocnemius muscles. Inoue et al [4] performed electromyographic analyses in 12 patients with PCL-deficient knees to compare electrical activity in the quadriceps, hamstring, and gastrocnemius muscles between the uninjured and involved knees. The authors reported that before generation of flexion torque, the gastrocnemius muscle was significantly electrically activated earlier in the PCL-deficient knees than in uninjured knees.…”
Section: Discussionmentioning
confidence: 99%
“…Tibone et al and Inoue et al also discovered that PCL-deficient knees have early activation of the gastrocnemius-soleus complex during activity, and therefore advocated that this compensation mechanism be emphasized in rehabilitation programs. 12,19 During the terminal stance, the gait adaptation and asymmetry of the asymptomatic PCL-deficient group were the most significant. This result concurred with the previous findings that the role of PCL in the gait cycle is the most important during terminal stance.…”
Section: Discussionmentioning
confidence: 99%